Syntax - Theory and analysis : an international handbook. - Kiss, Tibor, 1962-; Alexiadou, Artemis, 1969- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2015)
The handbook offers an overview of syntactic theory and analysis, in terms of different theories, different languages, and different methods. The Handbook presents the state of art in syntactic analysis, also dealing with the methodology employed, and the rules of argumentation required to achieve such analyses for a wide range of phenomena.